Hubungan Asupan Vitamin D Dan Selenium Dengan Indeks Bakteriologi Penderita Kusta Tipe MB (Multibacillary) : Systematic Literature Review - Putri, Fildzah Karunia; Yusyifak, Eka Zulfiana; Kardina, Rizki Nurmalya (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Background : As one of the infectious diseases that have a high prevalence until now, leprosy is a chronic transmission disease caused by infection with Mycobacterium Leprae. Apart from the standard MDT (Multidrug Therapy), nutritional support is a crucial component to restrict further infection severity. Vitamin D and selenium play essential roles as the primary defence against susceptibility. Methods : The systematic literature review was conducted using three international databases : PubMed, ResearchGate, and DOAJ, which were published between 2010 – 2020 using English or Indonesian. A total of 8 articles (2 articles identifying the correlation of selenium with leprosy, and 6 articles identifying the correlation of vitamin D with leprosy) using cross- sectional analytic and case-control analytic studies were included in this review. Results : The average serum levels of vitamin D and selenium in leprosy patients were lower than in healthy controls. This case was also found in Multibacillary leprosy patients compared to Paucibacillary leprosy patients. This serum levels can affect the bacteriological index, which is the higher the serum levels, the lower the bacteriological index. Disscusion : Serum vitamin D and selenium levels are affected by vitamin D and selenium intake, which can lead to a reduction in bacteriological index across all multibacillary leprosy patients. There is a negative correlation between vitamin D, selenium, and bacteriological index in patients with MB (Multibacillary) leprosy.Keywords:Leprosy, Vitamin D, Selenium, Bacteriological Index